Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class

Ex 7.4

Ex 7.4, 1

Ex 7.4, 2 Important

Ex 7.4, 3

Ex 7.4, 4

Ex 7.4, 5 Important

Ex 7.4, 6

Ex 7.4, 7

Ex 7.4, 8 Important You are here

Ex 7.4, 9

Ex 7.4, 10

Ex 7.4, 11 Important

Ex 7.4, 12

Ex 7.4, 13 Important

Ex 7.4, 14

Ex 7.4, 15 Important

Ex 7.4, 16

Ex 7.4, 17 Important

Ex 7.4, 18

Ex 7.4, 19 Important

Ex 7.4, 20

Ex 7.4, 21 Important

Ex 7.4, 22

Ex 7.4, 23 Important

Ex 7.4, 24 (MCQ)

Ex 7.4, 25 (MCQ) Important

Last updated at May 29, 2023 by Teachoo

Ex 7.4, 8 Integrate 𝑥^2/√(𝑥^6 + 𝑎^6 ) Let 𝑥^3=𝑡 Differentiating both sides w.r.t. x 3𝑥^2=𝑑𝑡/𝑑𝑥 𝑑𝑥=𝑑𝑡/(3𝑥^2 ) Integrating the function ∫1▒𝑥^2/√(𝑥^6 + 𝑎^6 ) 𝑑𝑥=∫1▒𝑥^2/√((𝑥^3 )^2 + (𝑎^3 )^2 ) 𝑑𝑥 Putting values of 𝑥^3=𝑡 and 𝑑𝑥=𝑑𝑡/(3𝑥^2 ) , we get =∫1▒𝑥^2/√(𝑡^2 + (𝑎^3 )^2 ) 𝑑𝑥 =∫1▒𝑥^2/√(𝑡^2 + (𝑎^3 )^2 ) . 𝑑𝑡/(3𝑥^2 ) =∫1▒1/√((𝑡^2 + (𝑎^3 )^2 ) ) . 𝑑𝑡/3 =1/3 ∫1▒𝑑𝑡/√(𝑡^2 + (𝑎^3 )^2 ) =1/3 [log|𝑡+√(𝑡^2 + (𝑎^3 )^2 )|+𝐶1] It is of form ∫1▒𝑑𝑥/√(𝑥^2 + 𝑎^2 ) =log|𝑥+√(𝑥^2 + 𝑎^2 )|+𝐶1 ∴ Replacing 𝑥 by 𝑡 and a by 𝑎^3, we get =1/3 log|𝑡+√(𝑡^2 + 𝑎^6 ) |+𝐶 =1/3 log|𝑥^3+√((𝑥^3 )^2 + 𝑎^6 ) |+𝐶 =𝟏/𝟑 𝒍𝒐𝒈|𝒙^𝟑+√(𝒙^𝟔+ 𝒂^𝟔 ) |+𝑪 ("Using" 𝑡=𝑥^3 )